The effects of wearing undersized lower-body compression garments on endurance running performance - Dascombe, B. J.; Hoare, T. K.; Sear, J. A.; Reaburn, P. R. J.; Scanlan, A. T. (International Journal of Sports Physiology and Performance, 2011)
Purpose: To examine whether wearing various size lower-body compression garments improves physiological and performance parameters related to endurance running in well-trained athletes. Methods: Eleven well-trained middle-distance runners and triathletes (age: 28.4 ± 10.0 y; height: 177.3 ± 4.7 cm; body mass: 72.6 ± 8.0 kg; VO2max: 59.0 ± 6.7 mL/kg/min) completed repeat progressive maximal tests (PMT) and time-to-exhaustion (TTE) tests at 90% VO2max wearing either manufacturer-recommended LBCG (rLBCG), undersized LBCG (uLBCG), or loose running shorts (CONT). During all exercise testing, several systemic and peripheral physiological measures were taken. Results: The results indicated similar effects of wearing rLBCG and uLBCG compared with the control. Across the PMT, wearing either LBCG resulted in significantly (P < .05) increased oxygen consumption, O2 pulse, and deoxyhemoglobin (HHb) and decreased running economy, oxyhemoglobin, and tissue oxygenation index (TOI) at low-intensity speeds (8-10 km/h). At higher speeds (12-18 km/h), wearing LBCG increased regional blood flow (nTHI) and HHb values, but significantly lowered heart rate and TOI. During the TTE, wearing either LBCG significantly (P < .05) increased HHb concentration, whereas wearing uLBCG also significantly (P < .05) increased nTHI. No improvement in endurance running performance was observed in either compression condition. Conclusion: The results suggest that wearing LBCG facilitated a small number of cardiorespiratory and peripheral physiological benefits that appeared mostly related to improvements in venous flow. However, these improvements appear trivial to athletes, as they did not correspond to any improvement in endurance running performance.